A STUDY ON ENGLISH LEARNING STYLES USED BY 11th GRADERS OF SMAN 1 KAUMAN TULUNGAGUNG - AMCHOSIHI, FIFASOH (Jurnal Ilmiah Mahasiswa FIB, 2013)
There are many factors affecting language learning, one of them is learning style. According to Reid (1995), a learning style refers to an individual’s natural, habitual, and preferred ways of absorbing, processing, and retaining new information and skill which persist regardless of teaching methods or content area. In this study, the writer analyzes the learning styles performed by science and social programs students of 11 graders of SMAN 1 Kauman Tulungagung and find out whether there is significance difference English learning styles between the two programs or not.This study is conducted by using quantitative approach The data of the study are collected by using questionnaire named Perceptual Learning Style Preference Questionnaire (PLSPQ) designed by Reid (1984). The samples of this study are a class of science program and a class of social program from the population that consists of 6 classes of science and 5 classes of social program.This study finds that 87.9% (29) students of science program choose group learnig style as their major learning style preference. It means that most of students of science program can learn English best when they learn in a group. While for social program students, 64.5% (22) of them place kinesthetic learning style as their major learning style preference, means that most of social program students can learn English well when they learn by experience.In addition, there is significance difference between science and social programs in applying English learning styles and most of students from those programs have multiple English learning styles. The major learning style preferences performed by science students from the highest untill the the lowest are group, kinesthetic, auditory, visual, tactile, and individual learning style.On the other hand, the learning styles performed by social program from the highest untill the lowest are kinesthetic, auditory, group, tactile, visual, and individual learning styles. So, science students tend to learn well when they work with others while social program will be better if they learn by experience. Keywords: learning styles, science program and social program, Perceptual Learning Style Preference Questionnaire (PLSPQ).